Coupling kinetic models and advection-diffusion equations to model vascular transport in plants, applied to sucrose accumulation in sugarcane - Uys, Lafras (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD (Biochemistry))--University of Stellenbosch, 2009.